Bio-coagulation using Cicer arietinum combined with pyrolyzed residual sludge-based adsorption for carwash wastewater treatment: A techno-economic and sustainable approach. (October 2022) - Dadebo, Derrick; Nasr, Mahmoud; Fujii, Manabu; Ibrahim, Mona G.
Abstract: The physico-chemical treatment of automobile service station wastewater (ASSW) generates large amounts of sludge with toxic compounds, requiring sustainable management practices to protect the environment. To the best of our knowledge, this is the first attempt to maintain the dual benefit of pollution reduction and biochar production via treating ASSW with an integrated coagulation/flocculation/adsorption and sludge pyrolysis system. Using Cicer arietinum powder as bio-coagulant, the optimum coagulation/flocculation factors were pH = 4, flash mixing speed = 170 rpm, and coagulant dosage = 2.26 g/L. This condition provided removal efficiencies of 88.35 ± 4.10 %, 60.30 ± 3.10 %, and 54.25 ± 2.81 % for turbidity, surfactant, and chemical oxygen demand (COD), respectively. Adsorption and inter-particle bridging were the main removal mechanisms involved in treating ASSW using C. arietinum, compared with sweep flocculation using alum. Sludge containing the C. arietinum bio-coagulant was subjected to thermal treatment by pyrolysis to synthesize biochar. This sludge-derived biochar showed promising pore size distribution, and surface morphology and functional groups. Biochar was used as an adsorbent to post-treat ASSW in a fixed-bed column with continuous feed, and the Thomas model exhibited a breakthrough time of 533 min for a designed flow rate of 30 m 3 /d. The overall removal efficiencies of turbidity, surfactants, and COD for the combined system reached almost 100 %, 99.93 ± 4.31 %, and 93.35 ± 3.88 %, respectively. The integrated physico-chemical and pyrolysis process showed a profitability scenario through wastewater reuse in carwash bays and biochar selling, maintaining a payback period of 5.8 yr. Graphical abstract: Unlabelled Image Highlights: Bio-coagulation/flocculation combined with fixed-bed adsorption column to treat ASSW. Coagulation-flocculation optimized at pH 4, mixing 170 rpm, C. arietinum dose 2.3 g/L. SEM/EDX, XRD, FTIR showed adsorption and inter-particle bridging by Cicer arietinum . Biochar prepared by bio-coagulant sludge pyrolysis was used in ASSW post-treatment. Profits of pollution reduction, effluent reuse, & biochar selling gave 5.8 yr payback.